Evaluation of the Benefits of the CSR Program of PT KPI RU II Sungai Pakning for Honey Beekeepers in Tanjung Leban Village - Nurfajrian Ahmad Fikri; Stefani Sinaga; Iswandi Iswandi (Jurnal Kebijakan Publik, 2025)
This study aims to evaluate the impact of the Corporate Social Investment (CSI) program initiated by PT Kilang Pertamina Internasional (KPI) RU II Sungai Pakning on the empowerment of honey beekeepers in Tanjung Leban Village, Bengkalis Regency. The program integrates economic, social, environmental, and community welfare objectives. This research uses a qualitative evaluation based on a logic model and counterfactual approach. Twelve participants were purposively selected, including core group members, nearby beekeepers, and local leaders actively involved from 2021 to 2025. Data were collected through in-depth interviews, focus group discussions, field observations, and document reviews using semi-structured instruments. Thematic analysis was conducted within the frameworks of the logic model, logframe, and sustainable livelihood approaches. The results show improvements in income, production capacity, and social networking; environmental conservation across 67 hectares of peatland; and reduced youth migration through ecotourism. The program also demonstrated cost-efficiency, institutional strengthening, and enhanced market competitiveness through product diversification and branding. Based on these findings, the program is evaluated as successful and effective as a contextual and sustainability-oriented social investment model. The implications highlight the relevance of this approach for impactful CSR policy design, sustainable rural development strategies, and participatory community-based conservation.